2007
DOI: 10.1080/03091900600687698
|View full text |Cite
|
Sign up to set email alerts
|

A re-evaluation of modelling of the current flow between electrodes: consideration of blood flow and wounds

Abstract: Electrical stimulation has been used for exercise, healing wounds, relieving pain, and strengthening muscle. The assumption is that current will flow predictably between electrodes and, therefore, there will be predictability in the clinical response to electrical stimulation. This may not be the case. The present investigation shows that considerable channelling of current occurs when the skin is heated or when there is a wound between the electrodes. By studying current movement in nutrient agar (a homogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This loss of energy is most likely due to the fat layer itself above the muscle. Previous studies describe a model explaining that the stimulation of muscle through skin is a capacitor in parallel with a high resistance and in series with a low resistance [25][26]. The electrical resistance of a capacitor is equal to ½pFC, in which F is frequency and C is capacitance [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This loss of energy is most likely due to the fat layer itself above the muscle. Previous studies describe a model explaining that the stimulation of muscle through skin is a capacitor in parallel with a high resistance and in series with a low resistance [25][26]. The electrical resistance of a capacitor is equal to ½pFC, in which F is frequency and C is capacitance [26].…”
Section: Discussionmentioning
confidence: 99%
“…For a square wave impulse, there is a significant direct current (during the plateau) and low frequency component which would not pass through the skin and into muscle. Sinusoidal waveforms, on the other hand, are able to transfer energy easier than square waves since the voltage is continually changing and occurs at a single pure frequency [26].…”
Section: Discussionmentioning
confidence: 99%
“…The difference may be due to electrode design. In studies in which the older carbonized rubber electrodes with electrode gel were compared to newer electrodes using hydro gel as an electrolyte (self adhesive electrodes), it was shown that the newer electrodes presently sold on the market have higher electrical resistance and, the current, irrespective of the width of the electrode, tends to disperse from the center of electrode where the lead wire is attached (Petrofsky et al 2006;Petrofsky and Schwab 2007). The newer electrodes use a resistive cotton wick to deliver current into the electrode and this tends to center the current near the wick and not across the full width of the electrode (Petrofsky et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, because of the lateral and series components of resistance in the skin, current dissipates both laterally and deep into tissue by a factor of 1/D 2 . Thus, for deep tissue stimulation, it takes excessively high currents which then cause sensory nerves in the skin to discharge causing pain and discomfort [4,22]. This is even more exacerbated in wounds.…”
Section: Discussionmentioning
confidence: 98%
“…Typically, the literature describes electric currents as moving predominantly in a direct line between the electrodes in a 2-electrode system [22]. Therefore, in wounds for example, *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%